2018
DOI: 10.5205/1981-8963-v12i5a231901p1409-1421-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados paliativos pediátricos: análise de estudos de enfermagem

Abstract: RESUMOObjetivo: analisar as evidências científicas acerca dos cuidados paliativos pediátricos.Método: estudo bibliométrico de publicações brasileiras realizado com 23 artigos disponíveis on-line, no período de 2012 a 2016 nas bases de dados LILACS, MEDLINE e BDENF, analisados pela estatística descritiva simples em figuras e posteriormente segundo a análise de conteúdo. Resultados: os artigos encontrados estão em revistas B1 e B2 majoritariamente, com publicações no ano de 2014. Os sujeitos mais estudados foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
0
4
0
13
Order By: Relevance
“…Para Sousa et al (2019) as crianças com doenças agudas ou crônicas que estão em risco de morte apresentam elevado quadro depressivo, que progride de forma acelerada e está ligado a fatores como a idade, dor, efeitos colaterais de medicamentos e atitudes negativas de acompanhantes. A depressão é um problema difícil de se superar e a equipe deve atuar em conjunto para oferecer um atendimento que garanta o bem-estar físico e mental, que melhore de fato a qualidade de vida e contribua para amenizar o sofrimento do paciente infantojuvenil durante este processo doloroso (Souza et al, 2018). Dias et al (2020) descreve que as crianças que estão em cuidados paliativos sofrem bastante com a dor e isso interfere diretamente no bem-estar do paciente, o que deixa os familiares estressados com a situação, pois já estão com o estado psicológico e emocional abalados.…”
Section: Discussionunclassified
“…Para Sousa et al (2019) as crianças com doenças agudas ou crônicas que estão em risco de morte apresentam elevado quadro depressivo, que progride de forma acelerada e está ligado a fatores como a idade, dor, efeitos colaterais de medicamentos e atitudes negativas de acompanhantes. A depressão é um problema difícil de se superar e a equipe deve atuar em conjunto para oferecer um atendimento que garanta o bem-estar físico e mental, que melhore de fato a qualidade de vida e contribua para amenizar o sofrimento do paciente infantojuvenil durante este processo doloroso (Souza et al, 2018). Dias et al (2020) descreve que as crianças que estão em cuidados paliativos sofrem bastante com a dor e isso interfere diretamente no bem-estar do paciente, o que deixa os familiares estressados com a situação, pois já estão com o estado psicológico e emocional abalados.…”
Section: Discussionunclassified
“…The survey of scientific researches that makes up this study points to the convergence of reviews that highlight the prevalence 9-14 and treatment modalities. 11,[14][15][16][17][18] It appears that its occurrence is constant, and often dramatic, being considered a medical emergency due to the strong physical, psychological, and social impact that results from it.…”
Section: Prevalence Of Pain and Treatment Modalities In Patients In Pmentioning
confidence: 99%
“…The importance of the association of pharmacological therapies complemented with recreational activities, such as arts, readings, and music for pain relief is highlighted. 16 Therefore, nurses who work in the implementation of care in the treatment of pain must use all technological resources and available, requiring knowledge of pharmacological and non-pharmacological modalities.…”
Section: Prevalence Of Pain and Treatment Modalities In Patients In Pmentioning
confidence: 99%
“…Another Brazilian review study (11) that aimed to analyze the scientific evidence about palliative care in pediatric nursing, indicated that only one scientific production covered children and adolescents as participants in the research.…”
Section: Introductionmentioning
confidence: 99%
“…Most publications still focus on family caregivers or the manifestations of symptoms, such as pain (11) . Thus, there is a need for studies engaged in giving voice to these subjects who experience such a delicate moment, permeated by various feelings in relation to mutilations and which are not reduced to physical and emotional pain, as they generate the experience of loss and uncertainty of the future (5) .…”
Section: Introductionmentioning
confidence: 99%